PENERAPAN METODE MOVING AVARAGE PADA PERAMALAN PERKARA ISBAT NIKAH - Atria; Wiwit Purwa Nurmayanti; Muhammad Gazali; Ristu Haiban Hirzi (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2020)
Marriage isbat is a determination, confirmation, and approval isbat marriage is a ratification of a marriage that has been heldaccording to the Islamic religion, but not recorded by KUA or allowed PPN. There are many East Lombok people who do nothave a marriage certificate, including those aged 43-70 years because of conditions that were not possible at the time, andunderage couples. This study uses secondary data in the form of marriage isbat data in the Selong Religious Court in 2019. Themethod used to analyze is the moving average method. The purpose of this study is to find out the most appropriate method amongforecasting or moving average with different orders, namely orders 3 and 5, and want to find out how much isbat maritalforecasting with the best method. The moving average results show that a good forecasting is find in the moving average of order5 with the number of isbat cases that entered Selong Religious Court is 286 cases.